Tinjauan Yuridis Terhadap Tindak Pidana Perdagangan Mie Kuning Basah dengan Menggunakan Bahan Formalin (Putusan Nomor 2796/Pid.Sus/2018/PN Mdn) - Wilbert Wilbert; Krisdayanti Wau; Venessa Chelsia (JURNAL MERCATORIA, 2020)
The practice of trading yellow noodles is often done by numerous irresponsible sellers because one of the chemicals they use as preservative is a very harmful substance, which is formalin. If consumed, formalin may cause allergy, cancer, stomach irritation, blood vomiting, and also death. Despite the fact that formalin is forbidden to be added in any kind of food products, it is still commonly found and being used by producers to ensure their goods last longer, stay fresh and can be sold with cheap prices. In this case, sellers or producers are more profit oriented and set aside customer’s health or safety. By using normative juridical research method, the writers intend to find out the liability which traders are held for selling formalin-preserved yellow noodles. In addition, legal protection to the victims who consumed it should be taken into account. National Agency of Drug and Food Control also have role in watching over and supervising food products that contain formalin.  Criminal offenders will be given sanction as they have violated Consumer Protection Law. The result of this research shows that the traders are fined as much as Rp 2.000.000 (two million rupiah) for breaking Consumer’s Law Constitution Number 8 Year 1999 article 62 paragraph (1) and article 8 paragraph (1).